History and Policy Challenges for Counter Radicalization Policy in Central Sulawesi - Roma Tressa; Nur Faizah (Universitas Muhammadiyah Palu, 2025)
Central Sulawesi is one of the former conflict areas and terrorism bases in Indonesia. The government continues to prevent the community especially the youth community from becoming radicalized. This research aims to find the right policy to prevent terrorism in the future. The data analysis technique used is Soft System Methodology (SSM). The method used is descriptive qualitative, by conducting interviews with the government, community and non-profit organizations. The research findings showed that the Integrated Action Plan program for Managing Social Conflict in the Poso Regency implemented dominated by a military sience 15 years ago but unable to prevent radicalization. A deliberative approach must be used to handle long-term radicalization, involving non-governmental actors as policy agents. The deliberative approach used the power of social capital, discussions with the citizen and involving the community in decision-making.